1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Proving the elements of a group are of finite order

  1. Feb 14, 2008 #1
    1. The problem statement, all variables and given/known data

    If N is a normal subgroup of a group G and every element of N and G/N has finite order, prove that every element of G has finite order.

    2. Relevant equations

    Um, a finite group element is given such that g^k = e (identity) for some integer k.
    We also know that the quotient of a group by a group is itself a group, with cosets as elements. If G/N is the quotient space, N is the identity element.

    3. The attempt at a solution

    The elements of N, call them n, have some finite order, so for some integer k we can say that n^k=e (the identity). The elements of the quotient group, G/N are the distinct cosets of N in G, so if they have some finite order m, then (Ng)^m=e=Ne (because N is the identity in the quotient group).

    I was hoping to do something like saying

    (ng)^m = ne ==> (n^m)*(g^m)= ne ==> n^(m-1)*g^m=e ==> somehow g^something =e.

    First of all, I am not sure if this is general enough to prove this for ALL cosets of G/N. Second, can I use little n instead of big N (we usually denote the cosets Ng. I think I can do the little one, though, because we're taking an element of N and operating on the left by some group element g). I don't know what else to do!! :confused:
  2. jcsd
  3. Feb 14, 2008 #2
    ooh, wait. Maybe someone can just tell me if this works... I am thinking that maybe

    (Ng)^m = N <==> (ng)^m=n. If that is true, then I can say (ng)^m = n ==> n^(m-1)*g^(m)=e ==> (n^(m-1)*g^(m))^k=e^k=e ==> (n^k)^(m-1)*g^(km))=e ==> g^km = e ==> g has finite order.

    Does that do it? Does that prove it for all g? Was my first assertion even valid?
  4. Feb 14, 2008 #3


    User Avatar
    Science Advisor
    Homework Helper

    Not quite. Try this. G/N has finite order. So for every g there is an m such that (gN)^m=N. (gN)^m=(g^m)N. If (g^m)N=N then g^m is in N. Can you fill in any missing arguments?
  5. Feb 14, 2008 #4
    Oh, that's very cool... I think we'd about be done then, because we already are given the fact that the elements of N are finite as well... So what mechanism is it that allows us to take the m inside the (gN) and just apply it to g? That's the part I am having trouble seeing.
  6. Feb 14, 2008 #5


    User Avatar
    Science Advisor
    Homework Helper

    An element of (gN)^m can be written as g*n1*g*n2*...*g*nm where the n's are in N, right? Since N is normal gN=Ng. So every g*n with n in N can also be written as n'*g where n' is a possibly different element of N. This lets you collect all of the g's together with the rest of the product being a product of n's. The same reason g1*N*g2*N=g1*g2*N.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook